2022
DOI: 10.1021/jacs.2c00239
|View full text |Cite
|
Sign up to set email alerts
|

Rh-Catalyzed Regio- and Enantioselective Allylic Phosphinylation

Abstract: Transition-metal-catalyzed branched and enantioselective allylic substitution of monosubstituted precursors with carbon, nitrogen, oxygen, sulfur, and fluoride nucleophiles has been well-established. However, such a selective carbon–phosphorus bond formation has not been realized probably due to the catalyst deactivation by the strong coordinating nature of phosphinylating reagents. Herein, we report a Rh-catalyzed highly regio- and enantioselective synthesis of allylic phosphine oxides in the presence of a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…31 P NMR monitoring experiments indicated the ligand displacement occurred within 20 min with 2 a′ as the nucleophiles (See Supporting Information for more details). The pre‐protected phosphinated reagent 2 a′′ reported by Li group, [10] was also explored with no conversion (entry 3). Screening different backbone‐derived P‐olefin ligands ( L2 to L3 ) showed that L1 provided the best stereoselectivity (entries 4, 5).…”
Section: Methodsmentioning
confidence: 99%
“…31 P NMR monitoring experiments indicated the ligand displacement occurred within 20 min with 2 a′ as the nucleophiles (See Supporting Information for more details). The pre‐protected phosphinated reagent 2 a′′ reported by Li group, [10] was also explored with no conversion (entry 3). Screening different backbone‐derived P‐olefin ligands ( L2 to L3 ) showed that L1 provided the best stereoselectivity (entries 4, 5).…”
Section: Methodsmentioning
confidence: 99%
“…26,27 However, current C(sp 2 )–P cross-coupling methods are limited by (1) high catalyst loadings (often 10 mol %) and, in some cases, alternative procedures (slow addition of H -phosphonate) 28 or phosphorus precursors ( e.g. , masked H -phosphonates) 29 required to overcome the inhibitory effects of phosphorus nucleophiles on metal catalysts given their strong coordination properties, (2) catalytic transfer hydrogenation, whereby (hetero)aryl halides are converted into (hetero)arenes due to the undesired reducing properties of H–P compounds, 30,31 (3) heating at high temperatures (often above 100 °C) to facilitate the C(sp 2 )–P bond-forming reductive elimination step, rendering the reactions potentially incompatible with complex substrates bearing sensitive functional groups, and (4) aprotic polar solvents, such as N , N -dimethylformamide (DMF), 24,32 which is classified as toxic and hazardous 33 and its use has been restricted by the European Commission. 34 Further exacerbating these problems, state-of-the-art C(sp 2 )–P cross-coupling methods fail to meet increasing demands for environmentally responsible chemical processes with low energy costs and loadings of precious transition metal catalysts in environmentally benign solvents ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a detailed mechanistic study, Breit proposed that the Rh σ-allyl complex is easily isomerized to the thermal dynamic stable chiral Rh-π-allyl complex in the presence of chiral bidentate ligand, accounting for the asymmetric transformation. Very recently, Li developed a Rh-catalyzed asymmetric allylic alkylation (AAA) reaction with a N , P , N -tridentate ligand ( L6 ) to further expand the scope of electrophiles and nucleophiles (Scheme b). It indicated that the third coordination is crucial to increase the oxidative addition ability of Rh complex to react with allylic substrates .…”
mentioning
confidence: 99%